AI-Driven Creativity in New Media: A Systematic Literature Review on Automated Content Generation and Personalization - Hashim, Mohd Ekram Alhafis; Puadi, Mohd Farizal; Albakry, Nur Safinas; Kamaruddin, Nor Hazlen; Md Nasir, Suraya; Nugrahani, Rahina (Journal of Advanced Research Design, 2025)
Artificial intelligence (AI) is reshaping modern media by automating content development and customisation, radically altering creative sectors. This systematic literature review (SLR) examines 30 papers from Scopus (45) and JSTOR (25), employing the PRISMA technique to ensure a thorough and structured synthesis of previous research. The findings indicate three main themes: (1) AI-Generated Content and Creative Automation: AI-powered techniques including natural language processing (NLP), generative adversarial networks (GANs), and deep learning models enable automated narrative, AI-generated text, digital artwork, and video content creation. These technologies improve efficiency and scalability while raising questions about originality, authenticity, and creative agency. (2) Personalization and Adaptive Media, which investigates how AI-powered recommendation systems, sentiment analysis, and predictive analytics might improve user engagement by adapting information to individual tastes. While these technologies improve audience participation, they also raise issues like as data privacy, algorithmic bias, anduser autonomy. (3) Ethical and Societal Implications of AI-Driven Media, with a focus on misinformation, algorithmic bias, and intellectual property rights, which require the creation of legislative frameworks to assure ethical AI application in media. The PRISMA approach drove the selection process, narrowing down an initial pool of 70 papers to the final 33 for in-depth study. The synthesis of these studies reveals that, while AI considerably improves creative productivity, its impact on authenticity, ethical considerations, and human-AI collaboration remains an important subject for future research. This study adds to the ongoing discussion on AI’s role in new media, providing insights for content creators, media professionals, and governments as they navigate AI-driven developments responsibly. More study is needed to address ethical concerns and develop best practices for incorporating AI into creative workflows while preserving artistic integrity and audience confidence.